Status of Nullity by Law the Agreement Due to Standard Clauses in the Consumer Protection Law - Sibagariang, Rudini; Yanto, Oksidelfa; Runaeni, Neni (Sinergi International Journal of Law, 2025)
Current legal issues greatly affect several aspects in the field of business law which often not infrequently end in civil lawsuits in court, although it has been clearly regulated in the Consumer Protection Law regarding several things that may be agreed upon in a contract, however, business actors often also ignore the rules that are prohibited from being made in the agreement, such as applying standard clauses which in the legal norms of the standard clauses in the Consumer Protection Law such things are not permitted, so that the situation becomes null and void, which in which such a situation can harm not only consumers but can also have an impact on the business actors themselves, in daily practice of course such things must be a serious concern not only in the field of business or business but in all aspects related to the law, especially those agreed upon in an agreement, because an agreement requires several provisions that cannot be simply ignored, although sometimes it seems that the existing agreement arises from existing problems, not actually prepared before a dispute occurs, because apart from the agreement being prepared to minimize more complicated disputes, it is also expected that there is good ethics in the implementation and obedience to follow what is it has been agreed that both individual subjects and legal entities such as companies are parties to an agreement.